Morphological description and DNA barcoding of Chaetocladius (Chaetocladius) elisabethae sp. nov. (Diptera: Chironomidae: Orthocladiinae) from the Moscow Region - Makarchenko, Eugenyi A.; Makarchenko, Marina A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2018)
Illustrated descriptions of the adult male, pupa and fourth instar larva, as well as DNA barcoding results of Chaetocladius (Chaetocladius) elisabethae sp. nov. in comparison with closely related species of Chaetocladius s. str. from the Moscow Region are provided. A reference 658 bp barcode sequence from a fragment of the mitochondrial gene cytochrome oxidase I (COI) was used as a tool for species delimitation. Comparisons with corresponding regions of COI between C. (s. str.) elisabethae sp. nov. and other species of the subgenus produced K2P genetic distances of 0.11–0.16, values well associated with interspecific variation. The barcodes of the new species were identical to the Chaetocladius sp. 2ES in BOLD systems. Molecular data were also used for the reconstruction of the phylogenetic relationships within the subgenus Chaetocladius s. str.